Royal Science...Toward Sustainable Educational Administration - Wongwatkasem, Wiralphat; Saelim, Tanaporn; Suriya, Nattapapa; Mansaraneeyatham, Suvijuk; Charoensanthia, Phot (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: The king’s science is a royal speech. Royal advice and the work of His Majesty King Bhumibol Adulyadej was given to the Thai people. It is a body of knowledge and wisdom. With the aim of development Prevent and solve problems to benefit the people and affect all mankind so that they can live a stable life. Peace and sustainability. Methodology: This study used document analysis and related research methods. Analyze the content and present it descriptively according to the study objectives. Results: The knowledge gained from various royal projects of His Majesty King Bhumibol Adulyadej has blasted the inside Planting forests in the hearts of the people, sufficiency, step by step, etc. Therefore, "The King’s Philosophy" is considered the "Science of Life" because it records the experiences of His Majesty’s work that enabled Thailand to overcome various crises in all dimensions. very well The King’s science is based primarily on the philosophy of Sufficiency Economy. This is a philosophy that has been given His Majesty’s guidance and guidance. It can lead to the goals of education management today by inserting it into educational administration teaching and learning. Including the implementation in daily life to aim for sustainable development and peaceful living for all Thai people. Conclusion: Knowledge from the Royal Project of His Majesty King Bhumibol Adulyadej presents the philosophy of Sufficiency Economy, the "science of life," promoting the practice of educational administration and Teaching, and promoting sustainable development and well-being of the Thai people.